Tinjauan Yuridis Dissenting Opinion terhadap Hakim Anggota Atas Perkara Tindak Pidana Penipuan - M Jordy Dwipayana; Maharani Nurdin (Wajah Hukum, 2021)
Contradicting judges' gathering in settling on legal choices is the embodiment of the appointed authority's individual flexibility to discover material truth. A definitive opportunity of presence is, not opportunity unbounded, but rather opportunity with a feeling of obligation and obligation. The review USES standardizing regularizing juridical strategies for study in which this kind of lawful exploration is normally alluded to as doctrinal law or library research. Since this review depends entirely on composed guidelines, it is firmly identified with libraries since it would require auxiliary information on the library. The 1981 law on criminal occasions (kuhap) decided that a court administering ought to be represented by a consistent agreement of the individuals from the adjudicators when such consistent agreement was unrealistic and the decision depended on the larger part by focusing on the "most productive" rule. The clarification of 182 stanzas (6) kuhap additionally states that it was recorded in the private program of the get together. Also, in this decision the outcome is a particular translation between the board of judges in seeing whether it is seen as proceeding or as an infringement of asas nebis in idem.